Smicromyrme ceballosi Suárez, 1959 and S. plantourianus Schwartz, 1986: two little known species new for Portugal (Hymenoptera, Mutillidae) - Matias, Rafael (Zootaxa, 2023)
The mutillid wasps (Hymenoptera, Mutillidae) of the Iberian Peninsula, and particularly of Portugal, are insufficiently researched. In this paper, two species in the genus Smicromyrme are added to the Portuguese fauna: S. ceballosi Suárez, 1959 and S. plantourianus Schwartz, 1986, both currently poorly known species. The former was hitherto recorded only from Spain, for which notes complementing the original description are given. The latter species was unexpected, as it was known only from Southern France and is thus also new for the Iberian Peninsula; given its original description may be considered insufficient by modern standards, a full redescription is here presented; the presently known localities in Portugal suggest S. plantourianus has a wide distribution and is probably a mainly Iberian species, which thus reaches in France the north-eastern limit of its distribution. In addition, the putative male of S. plantourianus is here newly described. A key to the Iberian Smicromyrme is presented, currently represented by 13 species and three subspecies.